The calls of Vietnamese bats: a major step toward the acoustic characterization of Asian bats - Dorottya Győrössy; Gábor Csorba; Kriszta Lilla Szabadi; Péter Estók; Vuong Tan Tu; Vu Dinh Thong; Neil M. Furey; Joe Chun-Chia Huang; Mao-Ning Tuanmu; Dai Fukui; Sándor Zsebők; Tamás Görföl (Scientific Reports, 2024)
Abstract Southeast Asia includes several global biodiversity hotspots and bats account for nearly one-third of mammal species currently known in the region. While acoustic methods have become widespread in bat research, basic information is often lacking on the echolocation calls produced by Asian bat species. Since such information can aid a wide variety of research and conservation initiatives, descriptions of the calls emitted by Asian bats are fundamental. The aim of our study was to provide a standardized analysis and description of the Vietnamese bat echolocation calls. We analyzed call recordings of 87 species arranged in eight families. This constitutes 74% of the echolocating bats presently known in Vietnam and includes the first call descriptions for five taxa. Our use of an open-source software and the deposition of recordings in the ChiroVox repository will facilitate comparative studies in Asia and the information we provide represents one of the most comprehensive bioacoustic databases for Asian bats to date.